Short communication: New analytical approach on (U-Th)/He dating of Fe-hydroxide with an example using goethite from the Amerasian Basin, Arctic Ocean - Yakubovich, Olga Valentinovna; Konstantinova, Natalia Pavlovna; Anosova, Maria Olegovna; Podolskaya, Mary Markovna; Adamskaya, Elena Valerevna (Copernicus Publications, 2024)
We propose a new analytical approach for (U-Th)/He dating of Fe-hydroxides, that includes sealing samples in quartz ampoules and demonstrates its suitability as a reliable tool for the investigation of geological processes. The (U-Th)/He ages of goethite clasts and vein from Fe- and Mn-oxide mineralization rocks recovered from the slope of Chukchi Borderland in the Amerasia Basin demonstrate remarkable reproducibility, yielding a weighted mean age of 8.6 ± 0.3 Ma (n=4) and 4.8 ± 0.4 Ma (n=2), respectively, providing insights into the Neogene mineralization history of the region. This study also focuses on the sample preparation technique, that might influence the (U-Th)/He ages. Our data indicate that a significant fraction of U can be leached from the goethite during sonication by distilled water which might result in over-dispersed (U-Th)/He ages.